Quantification of crystal morphology - Glicksman, M.E.; Koss, M.B.; Fradkov, V.E.; Rettenmayr, M.E.; Mani, S.S. (Journal of crystal growth, 1994)
Morphological measurement constitutes an important experimental subject in crystal growth and materials science, and is currently receiving renewed attention because of the rapid advances occurring in computer technology, coupled with the concomitant sharp reductions in the cost of digital image processing. Image processing applied to the quantification of microstructural images is currently being used in our laboratory to increase the understanding of interfacial dynamics during crystal growth and to analyze the kinetics of microstructural evolution. Quantification of microstructural and crystal growth morphologies, such as the measurement of dendritic tip radii, crystallite size distributions, and crystallite shapes, provides the geometric foundation needed for interpreting interfacial dynamics during crystal growth and an objective description of morphogenesis accompanying solid-liquid and solid-solid phase transformations. Automated methods employed, and, in part, developed by the authors to measure these morphological and kinetic parameters, using advanced statistical and stereological methods, are reviewed in this paper. Some of the techniques disclosed here are currently being refined even further to achieve improved precision in the quantification of crystal growth morphology.